The effect of pedalling cadence on maximal accumulated oxygen deficit - Hill, D. W.; Vingren, J. L. (European Journal of Applied Physiology, 2012)
Pedalling cadence influences the oxygen demand and the tolerable duration of severe intensity cycle ergometer exercise. Both of these variables are factors in the calculation of maximal accumulated oxygen deficit (MAOD), which is a widely accepted measure of anaerobic capacity. We were therefore interested in determining whether pedalling cadence affected the value of MAOD. Eighteen university students performed square wave cycling tests, using cadences of 60, 80, and 100 rev/min, at work rates selected to cause exhaustion in ~5 min. The oxygen demands for the tests were estimated by extrapolation from the steady-state oxygen uptake in two 4-min moderate intensity bouts performed using each cadence, and were greater at higher cadences. Times to exhaustion were shorter at higher cadences (368 ± 168 s at 60 rev/min > 299 ± 118 s at 80 rev min-1 > 220 ± 85 s at 100 rev/min). These factors conflated to produce values for MAOD that were not affected by cadence (52 ± 5 ml/kg = 52 ± 5 ml/kg = 52 ± 5 ml/kg). Similarly, the blood lactate concentrations measured 5 min post-exercise were not affected by the pedalling cadence (10.5 ± 2.1 mM = 10.8 ± 1.0 mM = 10.7 ± 2.0 mM). Although muscle contraction frequency influences many exercise responses, we conclude that the expression of anaerobic capacity is not affected by the choice of pedalling cadence.